Surto de tétano em búfalos (Buballus bubalis) no estado do Pará - BARBOSA NETO, José Diomedes (2012)
An outbreak of tetanus in Murrah buffaloes in Belém, state of Pará, Brazil, is described. The outbreak was observed in a flock of 250 buffaloes, 80 of which were vaccinated intra-muscularly in the croup against rabies. Four buffaloes fell ill 15 to 19 days after vaccination, one died after a clinical course of 2 days, one was submitted to euthanasia in extremis on the 7th day after the onset of symptoms, and two others recovered within 2 weeks after treatment with penicillin for 4 days and anti-tetanic serum. The first symptoms observed were prolapse of the third eyelid, especially when the animal was stimulated, followed by a rigid walk, as difficulty in inflexing the members and lateral recumbence with the members extended, besides very open eyelids, sialorrhea, hyperexcitability, erect ears and slight lockjaw, and food accumulation in the oral cavity. At post-mortem examination was found a focus of yellowish pus in the croup muscles, where the vaccine had been applied. At histopathology no significant alterations in internal organs were observed. Based on the clinical picture, the epidemic data and absence of histological lesions, the diagnosis of tetanus was established. The infection was considered to be due to the use of dirty needles used during vaccination.